Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

If g(x) = Vx and h(x) = x - 1, what is g(h(4))?


Sagot :

Answer:

3V

Step-by-step explanation:

given

h(x) = x - 1

g(x) = Vx

hence,

h(4) = 4 - 1 = 3

g(h(4))

= g(3)

= V(3)

= 3V

We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.